The Portrait of Matteo Ricci - Guillen-Nuñez, Cesar (Journal of Jesuit studies, 2014)
This article discusses a rather unusual portrait that depicts the Italian missionary Matteo Ricci (1552–1610), to be found today in the Gesù church in Rome. When it was first exhibited it aroused such excitement among Jesuits that it was displayed next to the portraits of St. Ignatius of Loyola and St. Francis Xavier. At an uncertain date, a small inscription was attached to the frame with Ricci’s name, his years of birth and death, and a statement that the painting had been exhibited in the vestibule of the Gesù residence in 1617, but that its artist was unknown. Although the painter’s name was disclosed as that of the Chinese-Macanese Jesuit brother You Wenhui (alias Manuel Pereira) in an account by Sabatino de Ursis soon after Ricci’s death, both the painter and his work have remained practically ignored by most researchers. This article studies the portrait and its creator from an art-historical perspective in much greater detail than previously. Stylistic and iconographic influences of Chinese Ming portraiture observable in the style of the work are identified, as are features from late sixteenth-century Counter-Reformation portraits. Certain aspects of Ricci’s contributions to Chinese science are also discussed, along with a number of contemporary theological arguments that tell us much about the nature of the portrait, its subject, its creator, and its deep spiritual significance.